The Non-Ergot Derived Dopamine Agonist Quinagolide as an Anti-Endometriotic Agent - Akyol, Alpaslan; Kavak, Ebru; Akyol, Hadice; Pala, Sehmus; Gursu, Ferit (Karger, 2017)
Aim: The study aimed to investigate the efficacy of a dopamine agonist, quinagolide, on experimentally induced endometriosis in a rat model. Methods: Twenty female Wistar rats were used in this experiment. Endometriosis was surgically induced by transplantation of autologous endometrial tissue. A second laparotomy was performed 4 weeks after the first one to assess the pre-treatment implant volumes, and peritoneal lavage with saline solution was performed to assess the peritoneal cytokine levels. Rats were randomized to treatment with quinagolide or saline. At the end of the treatment period, a third laparotomy was performed to compare pre- and post-treatment implant volumes and cytokine levels within the groups. Implants were excised to compare glandular tissue (GT) and stromal tissue (ST) scores between the groups. Results: In the quinagolide group, post-treatment volume was statistically significantly reduced compared with pre-treatment volume (p = 0.01). There were significant decreases in interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF) levels in peritoneal fluid samples in quinagolide-treated rats when compared to pre-treatment levels (p = 0.03 and p < 0.01). Histopathologically, both GT and ST scores were significantly lower in the quinagolide group compared to the control group (p = 0.01 and p = 0.02). Conclusions: Quinagolide caused a significant regression in endometriotic implants and it also significantly reduced the levels of IL-6 and VEGF in peritoneal fluid. (C) 2016 S. Karger AG, Basel
Keywords: Endometriosis; Quinagolide; Rat